Comparative acute toxicity of two phytosanitary molecules, lambda-cyhalothrin and acetamiprid, on Nile Tilapia (Oreochromis Niloticus) juveniles. Issue 7 (3rd July 2019) - Guedegba, Nicresse L.; Imorou Toko, Ibrahim; Agbohessi, Prudencio T.; Zoumenou, Berny's; Douny, Caroline; Mandiki, Syaghalirwa N.M.; Schiffers, Bruno; Scippo, Marie-Louise; Kestemont, Patrick
Abstract: This study aimed to compare the toxicity for fish of two active ingredients (lambda-cyhalothrin-20 g L −1, a pyrethroid, and acetamiprid-15 g L −1, a neonicotinoid) which are components of a commercial insecticide (Acer 35 EC) used in cotton crop in many West African countries. The juveniles of Oreochromis niloticus (4.01 ± 0.34 g, mean body weight) were exposed for 96 h to increasing concentrations of active ingredients (lambda-cyhalothrin and acetamiprid) or a mixture similar to Acer 35 EC (composed by 20 g of chemical compound lambda-cyhalothrin and 15 g of acetamiprid dissolved in 1 L of acetone). The experiments were carried out under controlled conditions in aquaria according to OECD Guidelines. During the experiments, the behavioral responses (loss of balance, color change, hyperactivity, etc.) that usually precede death were observed in exposed fish. Mortalities were recorded in each aquarium and the LC50 -96h of each chemical was determined. The LC50 -96h obtained were respectively 0.1268, 0.0029, 182.9 and 0.5685 ppm for Acer 35 EC, lambda-cyhalothrin, acetamiprid and mixture. All insecticides used in this study had profound impact on Nile tilapia behavior which may confirm the neurotoxicity of each single active compound as well as of their mixture.